Proceedings ASEAN workshop on food irradiation : (ASEAN Food Handling Bureau, 1985)
This book introduce about food irradiation, state of the art. ASEAN country papers on food irradiation. Economics of food irradiation. Food irradiation - institutional issues. Report of the panel on the worshop findings and recommentdations list of participants